Consumer behaviour towards voluntary carbon credits - SANTOS, Rennan Carvalho dos (2025)
This thesis explores consumer behaviour toward voluntary carbon credits by integrating Norm Activation Theory (NAT), Social Innovation Theory (SIT), and the Theory of Planned Behaviour (TPB). This research employs a quantitative approach, using data from 431 respondents, analysed with structural equation modelling (SEM), to identify key psychological and social factors influencing the intention to purchase voluntary carbon credits. These factors include attitude, subjective norms, perceived behavioural control, trust, novelty seeking, awareness of consequences, attribution of responsibility, and personal norms. The findings underscore the significance of these factors in shaping consumer purchase intentions. Additionally, they highlight the critical role of consumer education, transparent market practices, and innovative strategies to enhance consumer trust and engagement within the voluntary carbon market. Theoretical contributions involve advancing behavioural models through interdisciplinary integration, while practical implications extend to policymaking, business strategies, and consumer awareness campaigns. This study highlights the essential role of consumer participation in climate change mitigation and provides actionable insights to promote sustainable consumption and strengthen global efforts to achieve net-zero emissions.